Wolf (Canis lupus) Predation of a Polar Bear (Ursus maritimus) Cub on the Sea Ice off Northwestern Banks Island, Northwest Territories, Canada - Richardson, E.S.; Andriashek, D. (ARCTIC, 2009)
We describe the apparent predation of a polar bear (Ursus maritimus) cub by wolves (Canis lupus) on the sea ice just off the northwest coast of Banks Island, Northwest Territories, Canada. On 20 April 2004, while following the tracks of a female bear and two cubs-of-the-year in the snow during a helicopter survey, we noted that the bear tracks had been joined by several sets of wolf tracks. After following both sets of tracks for about 1 km, we observed a disturbed area in the snow with numerous overlying tracks. Upon landing and searching the site, we found the remains of a polar bear cub that the wolves had successfully separated from its mother and killed. This is only the second documented observation ever made of a polar bear killed by wolves. Nous décrivons la prédation apparente d’un ourson polaire (Ursus maritimus) par des loups (Canis lupus) sur la glace marine, tout près de la côte nord-ouest de l’île Banks, dans les Territoires du Nord-Ouest, au Canada. Le 20 avril 2004, après avoir suivi les traces d’une ourse et de deux oursons de l’année dans la neige lors d’une inspection en hélicoptère, nous avons remarqué que les traces d’ours avaient été rejointes par plusieurs séries de traces de loups. Après avoir suivi les deux séries de traces sur environ un kilomètre, nous avons remarqué que la neige avait été dérangée et que les traces se recoupaient beaucoup. Nous avons atterri, fouillé l’emplacement et trouvé les restes d’un ourson polaire que les loups avaient réussi à séparer de sa mère pour le tuer. Il ne s’agit là que de la deuxième observation à n’avoir jamais été recensée à propos de loups ayant tué un ours polaire.